Incorporating carbon sequestration toward a water-energy-food-carbon planning with uncertainties - Qiting Zuo; Qianwen Li; Lan Yang; Rui Jing; Junxia Ma; Lei Yu (iScience, 2023)
Summary: Water-energy-food nexus (WEFN) is the core content in the United Nations 2030 Agenda for Sustainable Development. However, the value of soil and crops’ carbon sink function has not yet been fully considered in the managment practices of WEFN system. Here, we developed a water-energy-food-carbon nexus (WEFCN) planning framework that incorporates carbon sequestration and multiple mathematical optimization methods into the practical WEFN management for Henan Province, which is one of major grain-producing areas in China. Uncertainties from multiple objectives, scenarios, and different stakeholder interests are captured. We found that wheat has the largest carbon sequestration, followed by corn and oil-bearing crops, while other crops have implicit carbon sequestration. Since chemical fertilizer produces the most carbon emissions, the usage of chemical fertilizer needs to be reasonably controlled. Overall, the proposed framework supports optimal decision-making for regional-scale WEFCN management and further unlocks the hidden value of agricultural carbon mitigation.